KOMPETENSI GURU DALAM MENINGKATKAN KINERJA GURU SERTA MENINGKATKAN PROFESIONALISME SEORANG GURU - Asi, Asi; Nuraini Meltari; Jesi Alexander (CV SWA Anugrah, 2023)
This research aims to describe and find out how professional competency knowledge of prospective teachers improves teacher performance and increases student learning motivation on student learning outcomes. The journal we created took data from several journals related to teacher professionalism. Through continuous improvement and development of performance, it is hoped that student guidance, teaching and training efforts can develop and increase the effectiveness of the teaching and learning process. To increase professionalism, teachers are required to understand the demands of existing professional standards and achieve the required qualifications and competencies. In the. Apart from that, teachers are also expected to be able to build good and broad relationships with their colleagues through professional organizations and develop a work ethic or work culture that prioritizes high quality service to consumers. There is a positive and significant influence between teacher competence on overall student learning outcomes. There is a positive and significant influence between student learning motivation on overall student learning outcomes.